Red blood cell distribution width to albumin ratio as a novel predictor for mortality in chronic obstructive pulmonary disease patients: Results from the cohort study of NHANES, 1999–2018 - Guoxin Zhang; Beizheng Xu; Xiaoyun Zhao (PLoS ONE, 2025)
Objectives To investigate the association of red blood cell distribution width (RDW) to albumin ratio (RAR) with mortality in chronic obstructive pulmonary disease (COPD) patients. Methods We selected 1,652 patients with COPD from the National Health and Nutrition Examination Survey (NHANES) 1999-2018, who were categorized into four groups according to the RAR quartiles. Kaplan-Meier curves, restricted cubic splines and the Cox proportional hazard model were used to evaluate the associations between RAR and all-cause mortality and chronic lower respiratory disease (CLRD) mortality in the COPD patients. Subgroup analyses were performed to check the interaction of the different characteristics. Results There were 640 deaths during follow-up, of which, 145 were from CLRD. Kaplan-Meier curves indicated COPD patients with higher RAR had significantly increased all-cause mortality and CLRD mortality. Multivariate Cox regression analyses showed HR of Q4 RAR was 2.88 (95% CI 2.18 - 3.81, p < 0.0001) for all cause-mortality and 3.39 (95% CI 1.76 - 6.53, p < 0.001) for CLRD mortality, compared with Q1 RAR. Restricted cubic splines analysis indicated a dose-response between RAR and risk of all-cause and CLRD mortality (p for non-linearity < 0.001). Conclusion RAR had an independent association with all-cause mortality, especially CLRD mortality, in COPD patients. RAR has potential as a novel and promising predictor to identify COPD individuals with high mortality risk.